OPTIMALISASI PRODUKSI MEUBEL PADA BALAI LATIHAN PENDIDIKAN TEKNIK (BLPT) KAATEN, KOTA TOMOHON - Ruth Elisa Simamora; Agnes E. Loho; Leonardus R. Rengkung (Sam Ratulangi University, 2018)
This study aims to determine the optimization of products, resource use and sensitivity of production resources in furniture BLPT kaaten. The study was conducted from April 2017 to August 2017. The data used were primary and secondary data. Primary data is obtained from direct observation of company condition and interview with related parties of research in company while secondary data obtained from company include cost data, raw material, rescue material, human labor and machine worker. The method used in this reswarch is case study. The data analysis used is Linear Programming with the help of using software LINDO Version 6.1. The results show that BLPT Kaaten has been operating optimally producing 76 church benches within 100 days with RP profits. 77.615.470. The limiting resource in the production of KUDENBLPT furniture is the manpower of the finishing department. Resource sensitivity sensitive to the decrease of the availability of raw materials are brass hinges, sis locks, leaf size 3 and leaf knob size 3.5.